2016
DOI: 10.3390/d8040021
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Sponge Biodiversity in the Pilbara, Northwestern Australia

Abstract: This study assessed the biodiversity of sponges within the Integrated Marine and Coastal Regionalisation for Australia (IMCRA) bioregions of the Pilbara using datasets amalgamated from the Western Australian Museum and the Atlas of Living Australia. The Pilbara accounts for a total of 1164 Linnean and morphospecies. A high level of "apparent endemism" was recorded with 78% of species found in only one of six bioregions, with less than 10% confirmed as widely distributed. The Ningaloo, Pilbara Nearshore and Pil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 69 publications
0
10
0
1
Order By: Relevance
“…The WN site also had higher demersal fish richness than the control sites in most surveys which suggests that habitat composition is a driver of diversity in these demersal communities, as has been found elsewhere on the NWS (Anon, 2019 ). The Pilbara Offshore mesoscale region, within which the study sites are located, is a biodiversity hotspot for sponges (Fromont et al, 2016 ). However, as much of the macrobenthos biomass was removed by seabed trawling (Sainsbury et al, 1993 ), most of the habitat in this region has been simplified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WN site also had higher demersal fish richness than the control sites in most surveys which suggests that habitat composition is a driver of diversity in these demersal communities, as has been found elsewhere on the NWS (Anon, 2019 ). The Pilbara Offshore mesoscale region, within which the study sites are located, is a biodiversity hotspot for sponges (Fromont et al, 2016 ). However, as much of the macrobenthos biomass was removed by seabed trawling (Sainsbury et al, 1993 ), most of the habitat in this region has been simplified.…”
Section: Discussionmentioning
confidence: 99%
“…This area was historically characterized by established macrobenthos communities made up of sponges, gorgonians, and soft corals on flat, sand inundated pavement (Evans et al, 2014 ). These macrobenthos communities were largely removed by pair‐trawling operations in the 1960s and 1970s (Fromont et al, 2016 ; Sainsbury et al, 1997 ). Previous studies on both platforms and pipelines on the NWS have found significant macrobenthos habitat associated with these structures, and abundance and richness of fish was higher on pipelines than on nearby natural habitats (Bond, Langlois, et al, 2018 ; Bond, Partridge, et al, 2018 ; McLean et al, 2018 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cover of benthic biota on both platforms was high, yet diversity is unknown given that it is very di cult to identify many corals and sponges to genus or species level without physical examination of specimens. Thus, while a high diversity of biota is known for this region (Richards and Rosser 2012;Fromont et al 2016), few distinct groups could be identi ed on platforms. This highlights the challenges of utilising imagery, no matter the quality, to assess the diversity of benthic communities where specimen collection or physical assessment is required.…”
Section: Discussionmentioning
confidence: 99%
“…The body architecture of most representatives of the Ianthellidae is characterized by a fan-shaped form [43][44][45]. In these sponges, tissues are localized on and within a mechanically rigid and dark-reddish pigmented meshwork which is produced by interconnected microtubular chitinous fibers (for details, see [30]).…”
Section: Isolation Of 3d Chitin Scaffoldsmentioning
confidence: 99%